IDENTIFIKASI POLA RUANG WILAYAH PESISIR KABUPATEN ACEH JAYA DALAM UPAYA PENGURANGAN RISIKO BENCANA TSUNAMI Studi Kasus : Gampong Babah Ie Kecamatan Jaya Kabupaten Aceh Jaya - Irwansyah .; Mirza Irwansyah; Syamsidik . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
This study aims to analyze the spatial patterns that have been prepared in the Spatial Plan of the Regency in Gampong Babah Ie in the face of the tsunami disaster in order to contribute thoughts to the Local Government of Aceh Jaya Regency in preparing or revising the Regional Spatial Plan of Aceh Jaya Regency in the face of disaster as well this study is expected to be able to increase knowledge, especially related to the study of land area pattern toward tsunami disaster in effort to reduce disaster risk in coastal area. The research method in this study is qualitative with descriptive approach. Data collection was conducted by collecting primary data and secondary data. The result of this study concluded that Aceh Jaya Regency Spatial Plan of 2014-2034 has considered tsunami risk reduction. However, in some coastal areas precisely in Gampong Babah Ie and surrounding areas, it has not been accommodated the space for coastal border or green belt area as a particular protected area in coastal areas. Appropriate mitigation efforts in disaster risk reduction in this area is to revise the Qanun RTRWK of Aceh Jaya Regency 2014-2034 by making allotment of coastal border and green belt, also to socialize the legislation and regulation concerning spatial plan of area to all community in Jaya Sub-regency generally and Gampong Babah Ie and its surrounding areas in particular.